MicroRNA-Mediated Host-Pathogen Interactions Between Bombyx mori and Viruses - Awais, Mian Muhammad; Shakeel, Muhammad; Sun, Jingchen (Frontiers in Physiology, 2021)
MicroRNAs (miRNAs), small non-coding RNAs of about 22 nucleotides, have been reported to regulate gene expression at the post-transcriptional level and are involved in several biological processes such as immunity, development, metabolism, and host-pathogen interactions. Apart from miRNAs encoded by the host, miRNAs produced by pathogens also regulate host genes to facilitate virus replication and evasion of the host defense responses. In recent years, accumulated studies suggest that viral infections alter the host miRNAs expression profile, and both cellular and viral miRNAs may play vital roles in host-pathogen interactions. Bombyx mori, one of the critical lepidopteran model species, is an economically important insect for silk production. The mechanism of interaction between B. mori and its pathogens and their regulation by miRNAs has been extensively studied. Therefore, in this review, we aim to highlight the recent information and understanding of the virus-encoding miRNAs and their functions in modulating viral and host (B. mori) genes. Additionally, the response of B. mori derived miRNAs to viral infection is also discussed. A detailed critical view about miRNAs' regulatory roles in B. mori-virus interactions will help us understand molecular networks and develop a sustainable antiviral strategy.